2021
DOI: 10.1016/j.omtn.2021.05.008
|View full text |Cite
|
Sign up to set email alerts
|

ceRNA regulatory network of FIH inhibitor as a radioprotector for gastrointestinal toxicity by activating the HIF-1 pathway

Abstract: Given the relentless renewal ability of intestinal crypt-base stem cells, small intestine in the gastrointestinal (GI) tract is more vulnerable to radiation-induced disruption. Through promoting epithelial integrity and reducing intracellular reactive oxygen species (ROS) levels, hypoxia-inducible factors (HIFs) have been proved to exhibit radioprotective effects in the GI tract. Therefore, enhancing stability or transcriptional activity of HIFs might be a therapeutic strategy for developing radioprotectors. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…FIH may be part of the regulatory network connecting hypoxia and inflammation, as FIH alters IL-1β-induced NF-κB activity and is relevant for the inflammatory response in the gut in vivo . 12 , 14 , 15 Nonetheless, the extent of contribution of FIH activity to inflammation as well as the molecular mechanisms that connect FIH and inflammation are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FIH may be part of the regulatory network connecting hypoxia and inflammation, as FIH alters IL-1β-induced NF-κB activity and is relevant for the inflammatory response in the gut in vivo . 12 , 14 , 15 Nonetheless, the extent of contribution of FIH activity to inflammation as well as the molecular mechanisms that connect FIH and inflammation are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with the FIH-selective pharmacologic agent N-oxalyl-D-phenylalanine (NOFD) was protective against irradiation-induced injuries of the gastrointestinal tract and FIH deletion in the colon epithelium attenuated chronic colitis. 14 , 15 We previously demonstrated that the enzymatic activities of FIH and PHD1 attenuate the major pro-inflammatory IL-1β signaling pathway. 12 Nonetheless, the general relevance and the detailed FIH-dependent regulation of inflammation remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the (to our knowledge) first use of NOFD was reported in animals. Repeated intraperitoneal injection of NOFD conferred radioprotection to the gastro-intestinal tract, which was suggested to be caused by increased HIF-1 transactivation activity (186). Analyzing the effect of 2-OG derivatives on FIH, 10 compounds were found to enhance FIH activity, whereas 17 compounds selectively inhibited FIH (118).…”
Section: Therapeutic Potential Of Pharmacologic Fih Inhibitionmentioning
confidence: 99%
“…Noticeably, Yang YW et al. ( 122 ) found that two circRNAs (circ_2909 and circ_0323) could promote the expression of HIF-1α and inducible nitric oxide synthase (NOS2) by acting as sponges for miRNAs. Furthermore, Demirci YM et al.…”
Section: Prospects Of the Clinical Application Of Circrnas In Covid-19mentioning
confidence: 99%